MYB, MYBL1, MYBL2 and NFIB gene alterations and MYC overexpression in salivary gland adenoid cystic carcinoma. Issue 5 (16th August 2017) - Fujii, Kana; Murase, Takayuki; Beppu, Shintaro; Saida, Kosuke; Takino, Hisashi; Masaki, Ayako; Ijichi, Kei; Kusafuka, Kimihide; Iida, Yoshiyuki; Onitsuka, Tetsuro; Yatabe, Yasushi; Hanai, Nobuhiro; et al.
Abstract : Aims: Adenoid cystic carcinoma (AdCC) is one of the most common salivary gland malignancies and the long‐term prognosis is poor. In this study, we examined alterations of AdCC‐associated genes, MYB, MYBL1, MYBL2 and NFIB, and their target molecules, including MYC. The results were correlated to clinicopathological profile of the patients. Methods and results: Using paraffin tumour sections from 33 cases of salivary gland AdCC, we performed a detailed fluorescence in‐situ hybridization (FISH) analysis for gene splits and fusions of MYB, MYBL1, MYBL2 and NFIB . We found that 29 of 33 (88%) AdCC cases showed gene splits in either MYB, MYBL1 or NFIB . None of the cases showed an MYBL2 gene alteration. AdCCs were divided genetically into six gene groups, MYB–NFIB ( n  = 16), MYB–X ( n  = 4), MYBL1–NFIB ( n  = 2), MYBL1–X ( n  = 1), NFIB–X ( n  = 6) and gene‐split‐negative ( n  = 4). AdCC patients showing the MYB or MYBL1 gene splits were associated with microscopically positive surgical margins ( P  = 0.0148) and overexpression of MYC ( P  = 0.0164). MYC expression was detected in both ductal and myoepithelial tumour cells, and MYC overexpression was associated with shorter disease‐free survival of the patients ( P  = 0.0268). Conclusions: The present study suggests that (1) nearly 90% of AdCCs may have gene alterations of either MYB, MYBL1 or NFIB, suggesting the diagnostic utility of the FISH assay, (2) MYB or MYBL1 gene splits may be associated with local aggressiveness of the tumours and overexpression of MYC, which is one of the oncogenic MYB/MYBL1 targets and (3) MYC overexpression may be a risk factor for disease‐free survival in AdCC.